Liquefaction of water on the surface of anisotropic two-dimensional atomic layered black phosphorus - Jinlai Zhao (Nature Portfolio, 2019)
Structural anisotropy of surfaces determines properties relevant for applications. Here the authors observe a relationship between the shape of water droplets forming on graphene, MoS2and black phosphorous and the surface structure, proposing a method to determine lattice orientation by optical microscopy.